The blue wolves of Mibu. 1 - Yasuda, Tsuyoshi (Kodansha USA Publishing, 2024)
Nio is an orphan who can't help dreaming of a better world. In this action-packed manga, he meets two men who show him how much a few swords can change history. This riveting samurai series from the creator of Days shares its setting with Rurouni Kenshin and chronicles the founding of the Shinsengumi by handsome and volatile men fighting for justice...and for themselves! It's 1863, the twilight of the shogunate, and Japan is on the cusp of monumental change. The streets of the nation's capital are soaked in blood as political upheaval and rising tensions between masterless, wandering ronin and government samurai set the stage for one of the most turbulent times in Japan's history. Young orphan Nio is no stranger to the harsh realities of the world, and yet he can't help but cling to his burning passion for justice and desire to change the world for the better. One day, he crosses paths with two men who will become central figures of the coming revolution: Hijikata Toshizo and Okita Souji, two of the founding members of a group of hated ronin known as the Miburo--who would later become known as the Shinsengumi. Inspired by the efforts of the so-called "Blues Wolves of Mibu," Nio decides to join the ranks to help carve a path to the world he wishes to see. But with new betrayals and reversals every day, will Nio be able to stay true to his conscience?"--